1990
DOI: 10.1159/000461138
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Beta and Gamma Sialoglycoprotein Associated with the Low-Frequency Antigen Ls

Abstract: This paper describes the association of the low-frequency antigen Lsa with high-molecular-weight variants of β- and γ-sialoglycoproteins (β-SGP, γ-SGP). The variant β-SGP, designated β^Ls^a, carries the Ge^3 epitope and the epitopes recognised by 3 murine monoclonal anti-β-SGP antibodies. The variant γ-SGP, designated γ^Ls^a, carries the Ge^2 and Ge^3 epitopes. Both β^Ls^a and y^Ls^a showed enhanced reactions in immunoblotting with anti-Ge3 sera - which may indicate the presence of 2 Ge3 epitopes on β^Ls^a and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…GPC.An", GPC.Dh", GPC.Ls" and GPC.Wb, and thus is located at the N-terminal domains of these glycoproteins (Reid et al, 1985;Macdonad & Gerns, 1986;Dahr et al, 1987;Telen & Bolk, 1987;Dahr et al, 1988Dahr et al, , 1989Daniels et af., 1988;McShane & Chung, 1989;Macdonald et al, 1990;Spring, 1991). Ge4 is also present at the N-terminal domain of the trypsin-resistant domain of GPC.Ge (Telen & Bolk, 1987;Dahr et af., 1988;Daniels et al, 1988;McShane & Chung, 1989).…”
Section: Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…GPC.An", GPC.Dh", GPC.Ls" and GPC.Wb, and thus is located at the N-terminal domains of these glycoproteins (Reid et al, 1985;Macdonad & Gerns, 1986;Dahr et al, 1987;Telen & Bolk, 1987;Dahr et al, 1988Dahr et al, , 1989Daniels et af., 1988;McShane & Chung, 1989;Macdonald et al, 1990;Spring, 1991). Ge4 is also present at the N-terminal domain of the trypsin-resistant domain of GPC.Ge (Telen & Bolk, 1987;Dahr et af., 1988;Daniels et al, 1988;McShane & Chung, 1989).…”
Section: Humanmentioning
confidence: 99%
“…The fact that the Ls" antigen is a consequence of the novel amino acid sequence on GPC.Ls" and GPD.Ls", which arises from the nucleotides at the boundary of the two copies of exon 3 in the GYPC.Ls' gene, has been demonstrated by using a synthetic peptide (TPTIMDTV-VTAEPDPG) specifically to inhibit the activity of anti-Lsa (King et al, 1991). Since GPC.Ls" molecules have amino acid residues encoded by duplicate copies of exon 3, both the GPC.Lsd and GPD.Ls" variants have two copies of the Ge3 antigen (Macdonald et al, 1990; see Fig. 2).…”
Section: Molecular Basis Of Gpcge Gpc Yus and Gpcls"mentioning
confidence: 99%
“…This arose partly as a result of examining red cells with the rare Leach phenotype that were not agglutinated by a monoclonal antibody with Gespecificity. Subsequently, low frequency antigens Wb, Ls" and Dha have been located on the same gene products, either normal or abnormal forms (Reid ef al., 1985;MacDonald et al, 1990;Spring et al, 1990). The chance of these low frequency antigens occurring in informative families that lack the high frequency antigens is very small; so the genetic linkage has only been demonstrated by immunoblotting techniques.…”
Section: Mnss Blood G R O U P Antigensmentioning
confidence: 99%
“…Macdonald et al [90] have shown that the low-frequency antigen Ls" is associated with abnormal forms of Glycophorin C and Glycophorin D, both of which are larger than their normal counterpart. Analysis of genomic DNA from an individual heterozygous for Ls" suggests that the Glycophorin C gene of Ls(a+) individuals contains an additional exon 3 [ fig.…”
Section: Gerbich Antigensmentioning
confidence: 99%